Contextualizing EFL Learners’ Proficiency in Using English Collocations - Sipayung, Rohdearni Wati; Saragih, Erikson (JEELS (Journal of English Education and Linguistics Studies), 2023)
Proficiency in using a foreign language cannot be separated from mastery of collocation in the target language. Although several previous studies have explored collocations in various forms of oral communication; however, few studies have investigated the context of collocation use and proficiency in collocation use by EFL learners. This study aims to describe the English collocation competence and collocational mistakes of Indonesian (EFL) students. A total number of 50 students from an English education department in Medan, Indonesia, served as the subjects. The research instrument was a 50-item Simple Completion Test that the researchers created themselves. It assessed students' understanding of four different lexical collocations: pure idioms, figurative idioms, free combinations, and restricted collocations. The findings showed that pure idioms were the most difficult for these students, while free combinations posed the fewest number of a challenge. Student performance on restricted collocations and figurative idioms were roughly equal. The student's inconsistent responses often showed a lack of proficiency with English collocations. It is concluded that poor first language transfer is to blame for the collocational errors made by EFL learners. The greatest way to get more proficient at using collocation while avoiding errors that have been identified thus far is to utilize it as frequently as feasible in English.